Roasting of the chillies - Mumbai Archive Project Team (Jio Institute, 2024)
The East Indian community masala is prepared differently from the method used in the Goan community, wherein the spices are pounded fresh without having been roasted. Drying and roasting are time-consuming processes, and there is no shortcut to achieving the same flavours without them. In the old days, family members came together to prepare the masala, a process that took place over several days. This fostered a sense of collaboration, thereby reinforcing the bonds that tie the East Indian community together.